Optimalisasi Media Edukasi Video dan Leaflet dalam Meningkatkan Kesadaran Perawat tentang Audit Keperawatan di Rumah Sakit - Rahma Dwi Syukrini; Hanny Handiyani; Nurhayati Nurhayati (Journal of Telenursing (JOTING), 2022)
This study aims to optimize video and leaflet educational media to increase nurse awareness about Nursing Audits at X Hospital. The method used is a pilot study. Data was collected through interviews, observation and questionnaires to 263 respondents. Data analysis was carried out using fishbone, preparation of a Plan of Action (POA) and educational media in the form of videos and leaflets. The results showed that the head of the room did not know the Nursing Audit process at the Hospital in the last two years. Unfavorable results were found in the organizational function of the head of the room (mean 2.2), especially statements about the involvement of nurses in the Nursing Audit process. In conclusion, a change in video educational media and leaflets is needed to increase nurses' understanding of Nursing Audits. Keywords: Nursing Audit, Nurse Awareness, Educational Media